PENGARUH LEVERAGE, LIKUIDITAS DAN PRODUKTIFITAS TERHADAP PERUBAHAN LABA (Studi Kasus pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia) - Dian Festiana (MEDIA, 2013)
This study aims to determine the effect of leverage ratios, liquidity and productivity to changes in earnings in manufacturing companies listed in Indonesia Stock Exchange. The data used are financial statements of companies listed in Indonesia Stock Exchange for three years are 2006 â€“ 2008. Population are used manufacturing companies listed in Indonesia Stock Exchange. Sampel selected for this study were 60 manufacturing firms the meet the criteria and group in 52 profitable companies and 8 of non profitable. Independent variables used in this studyÂ  were 14 financial ratios. The analytical method used is descriptive statistic and logistic regression using SPSS 13. The result showed that effect there is no significant effect between leverage to changes in income for liquidity whereas a significant different between earnings and liquidity to change in to productivity there is no significant effect between productivity with changes in earnings.